PERAN GURU PAI DALAM KEGIATAN PEMBIASAAN PAGI UNTUK MEMBENTUK KARAKTER RELIGIUS SISWA DI MAS AL-MUKARRIM PANCATENGAH KABUPATEN TASIKMALAYA - Nira , Nira; Mumu Turmudzi (Program Studi Pendidikan Agama Islam, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in the morning habituation activities and their impact on the development of students' religious character at Madrasah Aliyah Swasta (MAS) Al-Mukarrim Pancatengah. Character education is a crucial aspect of the Indonesian education system, particularly in shaping the moral values and religious character of students. Using a descriptive qualitative approach, this research examines how PAI teachers contribute to guiding, motivating, and facilitating morning habituation activities such as Dhuha prayer, reading the Qur'an, dhikr (remembrance of Allah), and brief religious studies. Data were collected through in-depth interviews, participatory observation, and documentation, and then analyzed using data reduction, categorization, as well as source and method triangulation to ensure the validity of the findings. The results of the study indicate that the morning habituation activities play a significant role in shaping students' religious character, improving their discipline, responsibility, and spiritual awareness. However, several challenges were identified in the implementation, including time constraints, varying levels of student participation, and limited school resources.